Some modern ethical Dilemmas regarding the Use of the Hippocratic Oath - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
History of the mankind knows different oath, which in their original forms, or somewhat modernized, have survived strict church courts, absolutist monarchy, despotic regimes, but even survived the people themselves. Beside the Hippocratic Oath, which, it seems, most durable and most disputed, we know for: oath of office ,the oath for citizenship, the oath which we take "under the penalty of criminal, civil and moral laws." However, the subject of our discussion will be only the first-mentioned Hippocratic oath, because of the numerous controversies caused for centuries in terms of its origin, authorship, authenticity on the one hand, and its importance while entering the medical profession, on the other hand.